Uranium in the Surrounding of San Marcos-Sacramento River Environment (Chihuahua, Mexico). (12th March 2012) - Rentería-Villalobos, Marusia; Cortés, Manuel Reyes; Mantero, Juan; Manjón, Guillermo; García-Tenorio, Rafael; Herrera, Eduardo; Montero-Cabrera, Maria Elena
Abstract : The main interest of this study is to assess whether uranium deposits located in the San Marcos outcrops (NW of Chihuahua City, Mexico) could be considered as a source of U-isotopes in its surrounding environment. Uranium activity concentrations were determined in biota, ground, and surface water by either alpha or liquid scintillation spectrometries. Major ions were analyzed by ICP-OES in surface water and its suspended matter. For determining uranium activity in biota, samples were divided in parts. The results have shown a possible lixiviation and infiltration of uranium from geological substrate into the ground and surface water, and consequently, a transfer to biota. Calculated annual effective doses by ingestion suggest that U-isotopes in biota could not negligibly contribute to the neighboring population dose. By all these considerations, it is concluded that in this zone there is natural enhancement of uranium in all environmental samples analyzed in the present work.